Independent language learning : building on experience, seeking new perspectives - Morrison, Bruce, 1956- (Hong Kong University Press ; Eurospan [distributor], 2011)
Independent learning is not a new concept for language educators but while teachers, curriculum designers and policy makers have embraced it as underpinning modern notions of education, it remains a dynamic and vibrant field for researchers and academics who aim to broaden its scope and deepen our understanding of how it may be applied most effectively both inside and outside the classroom. The contributors to this volume use their experience of applying the concepts related to independent learning in various geographical, cultural and pedagogical tertiary-level learning contexts to present ne.